2018
DOI: 10.1111/sms.13303
|View full text |Cite
|
Sign up to set email alerts
|

High‐density electromyography activity in various hamstring exercises

Abstract: Proximal-distal differences in muscle activity are rarely considered when defining the activity level of hamstring muscles. The aim of this study was to determine the inter-muscular and proximal-distal electromyography (EMG) activity patterns of hamstring muscles during common hamstring exercises. Nineteen amateur athletes without a history of hamstring injury performed 9 exercises, while EMG activity was recorded along the biceps femoris long head (BFlh) and semitendinosus (ST) muscles using 15-channel high-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 40 publications
3
51
0
1
Order By: Relevance
“…In comparison with the rest of the gait cycle, the magnitude of excitation in late swing has been reported as two to three times greater than during early swing and late stance, and the excitation during early stance is significantly greater than during late stance . In addition, studies of strength training exercises have demonstrated differences in proximal to distal regional excitation of the hamstring muscles during exercises such as the Nordic hamstring exercise, stiff‐leg deadlift, bent‐knee bridge, prone leg curl, and sliding leg curl . While differences in regional muscle excitation have not yet been investigated during high‐speed running, it is likely that this could provide further insight into muscle function and potential injury mechanisms, as injuries often primarily affect one region (the proximal musculo‐tendinous junction) …”
Section: Muscle Excitation Of the Bflh During High‐speed Runningmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with the rest of the gait cycle, the magnitude of excitation in late swing has been reported as two to three times greater than during early swing and late stance, and the excitation during early stance is significantly greater than during late stance . In addition, studies of strength training exercises have demonstrated differences in proximal to distal regional excitation of the hamstring muscles during exercises such as the Nordic hamstring exercise, stiff‐leg deadlift, bent‐knee bridge, prone leg curl, and sliding leg curl . While differences in regional muscle excitation have not yet been investigated during high‐speed running, it is likely that this could provide further insight into muscle function and potential injury mechanisms, as injuries often primarily affect one region (the proximal musculo‐tendinous junction) …”
Section: Muscle Excitation Of the Bflh During High‐speed Runningmentioning
confidence: 99%
“…37 In addition, studies of strength training exercises have demonstrated differences in proximal to distal regional excitation of the hamstring muscles during exercises such as the Nordic hamstring exercise, stiff-leg deadlift, bent-knee bridge, prone leg curl, and sliding leg curl. [42][43][44][45] While differences in regional muscle excitation have not yet been investigated during high-speed running, it is likely that this could provide further insight into muscle function and potential injury mechanisms, as injuries often primarily affect one region (the proximal musculo-tendinous junction). 46…”
Section: Muscle Excitation Of the Bflh During High-speed Runningmentioning
confidence: 99%
“…Despite this, as presented in Table 1, the use of eccentric muscle actions does not appear to place the youth athlete at greater risk of muscle damage than adults. Appropriate NHE prescription as well as other exercises that develop eccentric hamstrings strength [238][239][240] should be permissible in youth. Indeed, the NHE should form part of a holistic injury prevention program within youth to ensure that the hamstrings receive the specialist consideration that they require throughout youth [241].…”
Section: Eccentric Hamstrings Strengthmentioning
confidence: 99%
“…Furthermore, the noise they induce from the movement is severe, resulting in poor signal acquisition characteristics. For this reason, conventional EMG sensors require the application of foam tape or conductive gel to the adhesive surface of the devices to complement the adhesion property and signal acquisition performance of the skin to ensure the practical level of sensor capabilities [60][61][62][63][64][65]. One clear limitation of current technologies is the fact that the devices can only be used once, and not repeatedly.…”
Section: Introductionmentioning
confidence: 99%